Stories of our living ephemera: storytelling methodologies in the archives of the Cherokee National Seminaries, 1846-1907 - Legg, Emily, author; Utah State University Press, publisher (Colorado State University. Libraries, 2023)
Uses the Cherokee National Seminaries archive to recover institutional histories from colonized practices of research through student writing, pedagogical practices, and traditional 19th century Cherokee stories that provide Indigenous and matriarchal theoretical lenses.--Provided by publisher.
Origin stories: our stories, our ways, our knowledges -- Wolf wears (Eurocentric) shoes: indigenizing the archives -- Archives out of story: severed relations and Indigenous world views -- Storying Duyuk'ta together: Indigenous storytelling as rhetorical methodology -- Stories emerging from dusty boxes: finding Duyuk'ta at the Cherokee National Seminaries -- "Where bright thoughts like rivers flow": composing with and for the Cherokee Nation -- "To keep alive tradition": survivance and writing at the Cherokee National Seminaries -- Gadugi: working together (an epilogue of sorts).
Keywords: Cherokee National Female Seminary -- Archives; Cherokee National Male Seminary -- Archives; Cherokee Indians -- Education; Cherokee Indians -- Folklore